Jaranan : the horse dance and trance in East Java - Groenendael, Victoria M. Clara van; Yperen, Maria J.L. van (Leiden : KITLV Press, 2008)
The dramatic genre of the horse dance (jaranan) is part of an age-old Javanese tradition displaying wide local and regional variations.
Includes bibliographical references (pages [273]-284) and index.
English with some Javanese ; translated from the original Dutch.
Keywords: Folk dancing, Javanese -- Indonesia -- Jawa Timur; Ecstatic dance -- Indonesia -- Jawa Timur; Trance -- Indonesia -- Jawa Timur; Jawa Timur (Indonesia) -- Social life and customs